Water quality of a new social gray water treatment technology (Research, Society and Development, 2023)
The reuse of effluents, mainly gray water, after adequate treatment, appears as a viable alternative to a possible lack of water, mainly in the semi-arid region. The present work aims to evaluate the microbiological and physical-chemical quality of gray water submitted to treatment in a new social technology: the 'Olho d'água grey' and the possibilities of use in irrigation of family agriculture and watering of animals. The study was carried out over a period of three years (2020 to 2022) in a family farming area belonging to an associate of the Associação Christian de Base (ACB), located in Serra da Minguiriba (Chapada do Araripe), rural area of Crato- Ceará. Water samples were collected before and after treatment, and chemical, physical and microbiological analyzes were carried out. In all analyses, fecal coliforms were not detected and parameters such as pH, nitrate, nitrite, calcium, magnesium, iron, chlorides, electrical conductivity, turbidity, odor, met the requirements of national legislation. The results prove the efficiency of the 'Olho d'água grey' system, indicating the possibility of reuse of gray water in irrigation systems of family agriculture and in the watering of wild and domestic animals. Social technology such as the 'grey water eye' is extremely important for the semi-arid region, mainly to contribute to sustainable development, enhance family farming, reduce pollutant loads emitted in receiving bodies and contribute to the health of the rural family.